2023
DOI: 10.1155/2023/1481489
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance and Function of Neutrophils in the Endometriosis Systemic and Pelvic Microenvironment

Abstract: Endometriosis is a common inflammatory illness in which endometrial tissue grows outside the uterine cavity. Immune dysfunction is now widely acknowledged as the primary cause of endometriosis. The immune cell population represented by neutrophils is thought to play an essential role in the etiology, pathophysiology, and associated clinical outcome. There is growing evidence that neutrophils have a role in chronic and aseptic inflammatory diseases, and endometriosis patients have increased levels of neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…[37,38] The genes included in their models were as follows: PTGER2, FGF2, IGFBP3, ANGPTL4, DKK1, WNT16, SPP1, ZNF532, COLEC12, DPP7/2, YWHAB, MCM4, FBXO46, GLP2R, VSTM2A, and so on. [37,39,40] In our model, we included directly nine key EIOGs, and finally got a mode with the highest AUC reached 0.788, which indicated that EIOS alone play an important role in the CRC progression. We also proposed that a better prognostic model could be established based on a comprehensive understanding all these genes.…”
Section: Discussionmentioning
confidence: 94%
“…[37,38] The genes included in their models were as follows: PTGER2, FGF2, IGFBP3, ANGPTL4, DKK1, WNT16, SPP1, ZNF532, COLEC12, DPP7/2, YWHAB, MCM4, FBXO46, GLP2R, VSTM2A, and so on. [37,39,40] In our model, we included directly nine key EIOGs, and finally got a mode with the highest AUC reached 0.788, which indicated that EIOS alone play an important role in the CRC progression. We also proposed that a better prognostic model could be established based on a comprehensive understanding all these genes.…”
Section: Discussionmentioning
confidence: 94%
“…Absence of neutrophils/neutropenia impedes endometrial repair in mice [14]and also results in fetal abortions as they are critical for establishing utero-placental circulation [13]. Overinfiltration andactivation cause enhancement in the pathogenesis of endometriosis [15], cancer and auto immune diseases [7]. Therefore, for a better understanding of their regulation, role within the uterus, it is necessary to know their quantity, localization and distribution, during different stages of estrus cycle in physiological conditions [16].…”
Section: Introductionmentioning
confidence: 99%